THE EXISTENCE OF LAUJE TRADITIONAL JURISDICTION IN THE CRIMINAL JUSTICE SYSTEM - Moh Didi Permana (Omnibus Law Journal, 2022)
The handling of cases related to the principle of newbies in idem is a study of the application of the principle of newbies in idem so that the same case is not repeated at the court level. Nebis In Idem is a legal principle that applies in both civil and criminal law. In criminal law, this principle implies that a person may not be prosecuted twice because of an act that has received a decision that has permanent legal force. The explanation is in accordance with Article 76 paragraph (1) of the Criminal Code. Keywords : Implementation, Nebis In Idem, Judicial Decision